Learning from academic conferences - Popovic, Celia (Critical issues in the future of learning and teaching, 2018)
"In Learning from Academic Conferences, the editor combines research findings and practical advice aimed at ensuring organizers, attendees and administrators get the most from academic conferences. Contributors from the UK and Canada have pooled their experience and research findings to produce a guide in three parts. Starting with a focus on participants, moving onto presenters and finally addressing organizers, the authors provide comprehensive advice. Conferences are expensive in terms of time and resources; this book will ensure that investment is put to best effect."--Provided by publisher.